STUDENTS’ PERCEPTION ABOUT GOOGLE TRANSLATION TOOL IN LEARNING ENGLISH : (A Descriptive Study at Jabal Ghafur University) - Mustakim Sagita; Jamaliah Jamaliah; Nurul Balqis (Getsempena English Education Journal, 2021)
This research was aimed to know the students’ perception about Google Translation tool in learning English. The background of the research based on the raised of the use Google Translation tool among students. Therefore, the researcher conducts a research regarding students’ perception on the use of Google Translation tool in learning English. To answer the problem above, there are two research questions formulated. (1) how many percent students of English Department use Google Translation tool in learning English and (2) Students’ perception on the use of Google Translation tool in learning English. Meanwhile, to solve the research question that was already formulated, the researcher applied descriptive qualitative research design. There were two sets of questionnaire as instrument used in this research which were the first questionnaire to answer the first research question and the second questionnaire to answer the second research question. The respondents of this research were active students of English Department at Jabal Ghafur University in batch 2016-2019. All of them were chosen by using purposive sampling. The findings of this research showed that the students of English Department at Jabal Ghafur University used Google translation tool in learning English because sometimes they had difficulties in understanding English especially in translation activity. They utilize it to help them such as to translate, as dictionary, to check synonym and antonym, and to check pronunciation. Furthermore, they had a positive perception about Google Translation tool in learning English with majority of answers chosen by them were “agree” that it was helpful in learning English. In addition, there were also suggestions to students who use Google translation tool in learning English and the future researchers.